Value propositon in niche market segmentation for black belt cold brew coffee in order to capture target market - Felix, Gian; Permadi Iskandar, Budi (The Indonesian Journal of Business Administration, 2016)
Abstract. The purpose of this research is to formulate marketing strategy and marketing plan for Black Belt Cold Brew Coffee to capture its target market in Cold Brew Coffee industry geographically in South Jakarta. Black Belt Cold Brew Coffee is Startup Company that sell cold brew coffee product which specialized for combat sports gym. Established in Jakarta, Black Belt Cold Brew Coffee is facing urgency to compete and had to capture its target market through delivering its value proposition to its target market. Black Belt Cold Brew Coffee having advantage by specializing to sell only for combat sports gym as there are on demand for coffee product meanwhile there are unavailable coffee product in combat sports gym, therefor Black Belt Cold Brew Coffee is the first entrant for coffee product in combat sports gym.  By specializing to combat sports gym, it gives Black Belt Cold Brew Coffee niche market segmentation which result ability to compete with competitors through its channel distribution and also grant Black Belt Cold Brew Coffee suitable value proposition in combat sports gym which are fat burner and endurance that are useful to support combat sports workout. Methods which used in the research are the combination from quantitative and qualitative methodology. Interview and questionnaire are conducted to collect primary data and the results are analyzed to gathered secondary data. Those data will be used to validate the opportunities in the combat sports gym. It is conducted to generate marketing strategy to have competitive advantage for Black Belt Cold Brew Coffee. The value proposition will be communicated through marketing plan for niche market segmentation of Black Belt Cold Brew Coffee. The research result readjustment of product label and the selling price of the product which is intended to support the marketing strategy of Black Belt. Black Belt also has to generate another product variant to have capabilities to capture the target market by flavor preferences and Black Belt Cold Brew Coffee has to deliver the value proposition to the target market in combat sports gym by having promotional effort such as promotional price and informative poster of the benefits of consuming coffee and caffeine to show that Black Belt Cold Brew coffee offer valuable product for the visitor of combat sports gym.   Keyword: Marketing Strategy, Marketing Plan, Value Proposition, Black Belt Cold Brew Coffee Abstract. The purpose of this research is to formulate marketing strategy and marketing plan for Black Belt Cold Brew Coffee to capture its target market in Cold Brew Coffee industry geographically in South Jakarta. Black Belt Cold Brew Coffee is Startup Company that sell cold brew coffee product which specialized for combat sports gym. Established in Jakarta, Black Belt Cold Brew Coffee is facing urgency to compete and had to capture its target market through delivering its value proposition to its target market. Black Belt Cold Brew Coffee having advantage by specializing to sell only for combat sports gym as there are on demand for coffee product meanwhile there are unavailable coffee product in combat sports gym, therefor Black Belt Cold Brew Coffee is the first entrant for coffee product in combat sports gym.  By specializing to combat sports gym, it gives Black Belt Cold Brew Coffee niche market segmentation which result ability to compete with competitors through its channel distribution and also grant Black Belt Cold Brew Coffee suitable value proposition in combat sports gym which are fat burner and endurance that are useful to support combat sports workout. Methods which used in the research are the combination from quantitative and qualitative methodology. Interview and questionnaire are conducted to collect primary data and the results are analyzed to gathered secondary data. Those data will be used to validate the opportunities in the combat sports gym. It is conducted to generate marketing strategy to have competitive advantage for Black Belt Cold Brew Coffee. The value proposition will be communicated through marketing plan for niche market segmentation of Black Belt Cold Brew Coffee. The research result readjustment of product label and the selling price of the product which is intended to support the marketing strategy of Black Belt. Black Belt also has to generate another product variant to have capabilities to capture the target market by flavor preferences and Black Belt Cold Brew Coffee has to deliver the value proposition to the target market in combat sports gym by having promotional effort such as promotional price and informative poster of the benefits of consuming coffee and caffeine to show that Black Belt Cold Brew coffee offer valuable product for the visitor of combat sports gym.   Keyword: Marketing Strategy, Marketing Plan, Value Proposition, Black Belt Cold Brew Coffee